The risk-return tradeoff: are sustainable investors compensated adequately? - Christina E. Bannier; Yannik Bofinger; Björn Rock (Journal of Asset Management, 2023)
We investigate the returns from investing according to corporate social responsibility (CSR) criteria using factor model estimations for a large sample of U.S. firms over the period 2003–2017. To identify the CSR intensity that allows investors to optimize their portfolio returns for a given amount of risk, we relate factor-adjusted portfolio returns to a variety of risk measures. This consideration is important as equity risks have been shown to significantly decrease with CSR. Surprisingly, our results indicate that the lowest CSR-rated portfolios are able to outperform their higher CSR-rated counterparts: Not only do they show higher factor-adjusted returns but they also deliver higher return-to-risk ratios. This indicates that equity returns in our sample decrease even more strongly than the corresponding risks with rising CSR activity.
Keywords: G11; G12; O16; Q56; 330; Stock returns; Risk-return; CSR; ESG; Factor analysis